CORPORATE SOCIAL RESPONSIBILITY IN FAVOR OF IMPROVING EDUCATION IN SOCIETY (CASE OF PT PERTAMINA REFINERY UNIT VI BALONGAN) - Ilona Vicenovie Oisina Situmeang (Bricolage : Jurnal Magister Ilmu Komunikasi, 2017)
Corporate Social Responsibility (CSR) is an external activity of a corporate undertaken for the benefit of society. It is expected to facilitate good relationship between the corporate and society. The purpose of this research is to describe Corporate Social Responsibility activity in favor of improving education in society. Research method was using an approach of qualitative descriptive in the case of PT. Pertamina Refinery Unit VI Balongan. Data was collected through conducting in-depth interview, observing, and implementing FGD. The results showed that CSR activity was very beneficial to local society as many of them were be able to continue higher education. Furthermore, local government also found out that CSR has a measurable good impact in local human development index. A long-term goal of CSR is to develop quality human resources to sustain a better life for all. Keywords: Corporate Social Responsibility, Society, Education